Cosmic degeneracies – I. Joint N-body simulations of modified gravity and massive neutrinos. Issue 1 (8th March 2014) - Baldi, Marco; Villaescusa-Navarro, Francisco; Viel, Matteo; Puchwein, Ewald; Springel, Volker; Moscardini, Lauro
Abstract: We present the first suite of cosmological N -body simulations that simultaneously include the effects of two different and theoretically independent extensions of the standard Λ cold dark matter (ΛCDM) cosmological scenario – namely an f  ( R ) theory of modified gravity and a cosmological background of massive neutrinos – with the aim to investigate their possible observational degeneracies. We focus on three basic statistics of the large-scale matter distribution, more specifically the non-linear matter power spectrum, the halo mass function, and the halo bias. Our results show that while these two extended models separately determine very prominent and potentially detectable features in all the three statistics, when we allow them to be simultaneously at work these features are strongly suppressed. In particular, when an f  ( R ) gravity model with f R 0  = −1 × 10 −4 is combined with a total neutrino mass of Σ i m ν i = 0.4 eV, the resulting matter power spectrum, halo mass function, and bias at z  = 0 are found to be consistent with the standard model's predictions at the ≲10,  ≲20, and ≲5 per cent accuracy levels, respectively. Therefore, our results imply an intrinsic theoretical limit to the effective discriminating power of present and future observational data sets with respect to these widely considered extensions of the standard cosmological scenario.